1999
DOI: 10.4269/ajtmh.1999.60.215
|View full text |Cite
|
Sign up to set email alerts
|

Acute Chagas' disease in western Venezuela: a clinical, seroparasitologic, and epidemiologic study.

Abstract: Abstract.A clinical, parasitologic, and serologic study carried out between 1988 and 1996 on 59 acute-phase patients in areas of western Venezuela where Chagas' disease is endemic showed 19 symptomatic patterns or groups of symptoms appearing in combination with different frequencies. The symptomatic pattern with the highest frequency was that showing simultaneously fever, myalgia, headache, and Romaña's sign, which was detected in 20% of the acute-phase patients. Asymptomatic individuals and patients with fev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 15 publications
4
62
0
10
Order By: Relevance
“…They also attributed to the Chagas disease control program the reduction of the original endemic area from 750,000 km 2 to 365,000 km 2 , making an estimation of nearly 4 × 10 6 people living at risk of infection. Despite the apparent control attributable to the effect of the campaign against Chagas disease in Venezuela, there is, at present, a re-emergence of the disease judging for the increasing number of reported acute cases during the last decade (Parada et al 1996, 1997, Añez et al 1999. This information appears to be relevant taking into consideration that in just one rural area eight acute chagasic patients per year were diagnosed, with a mortality of 12.5% irrespective of the received treatment (Parada et al 1996, Añez et al 1999.…”
Section: Historical Remark Of Chagas Disease In Vene-zuelamentioning
confidence: 99%
See 1 more Smart Citation
“…They also attributed to the Chagas disease control program the reduction of the original endemic area from 750,000 km 2 to 365,000 km 2 , making an estimation of nearly 4 × 10 6 people living at risk of infection. Despite the apparent control attributable to the effect of the campaign against Chagas disease in Venezuela, there is, at present, a re-emergence of the disease judging for the increasing number of reported acute cases during the last decade (Parada et al 1996, 1997, Añez et al 1999. This information appears to be relevant taking into consideration that in just one rural area eight acute chagasic patients per year were diagnosed, with a mortality of 12.5% irrespective of the received treatment (Parada et al 1996, Añez et al 1999.…”
Section: Historical Remark Of Chagas Disease In Vene-zuelamentioning
confidence: 99%
“…In addition, there are still countries in South America where acute cases have been recently detected suggesting an active transmission of T. cruzi-infection. This is particularly true in Venezuela where 59 acute phase cases were detected from 1988 to 1996 in a restricted area in the Western part of the country (Parada et al 1997, Añez et al 1999.…”
mentioning
confidence: 99%
“…Since then, the recorded outbreaks of acute Chagas disease (ChD) have been as follows: between 1988-1996, 59 cases occurred in the western states of Venezuela (Añez et al 1999), after which nine cases involving two deaths occurred during the period of January 2006-March 2007 in the same endemic area (Añez et al 2007). In 2004 and 2006, the deaths of two children near Caracas were documented (Alarcón de ).…”
mentioning
confidence: 99%
“…Firstly, our survey could have overestimated the actual seroprevalence of T. cruzi infection. However, the method that we used, ELISA, offers a high reliability and is concordant with other serological methods such as direct agglutination test or indirect immunofluorescence antibody test (Añez et al 1999) and PCR (Brenière et al 2002). Furthermore, T. cruzi trypomastigote extract, with almost no cross-reactivity with other protozoan infections (Aznar et al 1997), has been shown to be an excellent reagent for detecting the infection in areas of low prevalence, and appears to be better than epimastigote extracts.…”
Section: Discussionmentioning
confidence: 63%